Download presentation
Presentation is loading. Please wait.
Published byAron Shelton Modified over 9 years ago
1
Algebra 2 Trig A Final Review 2007
2
#1 Hyperbola Center (0, 0) a = 8, b = 7, c = Vertices: (+8, 0) Foci: (, 0) Slopes of asymptotes: +7/8 Hyperbola Center (0, 0) a = 8, b = 7, c = Vertices: (+8, 0) Foci: (, 0) Slopes of asymptotes: +7/8
3
#2 y 2 = 121 - x 2 Circle: x 2 + y 2 = 121 Center: (0, 0) Radius = 11 Circle: x 2 + y 2 = 121 Center: (0, 0) Radius = 11
4
#3 y = 2(x - 2) 2 + 1 Parabola Center/Vertex: (2, 1) AOS: x = 2 DOO: up Focus: (2, 9/8) Directrix: y = 7/8 Parabola Center/Vertex: (2, 1) AOS: x = 2 DOO: up Focus: (2, 9/8) Directrix: y = 7/8
5
#4 6x 2 + 16y 2 = 96 Ellipse: Center: (0, 0) a = 4, b =, c = M vertices: (±4, 0) Foci: (, 0) LMA = 8 lma = Ellipse: Center: (0, 0) a = 4, b =, c = M vertices: (±4, 0) Foci: (, 0) LMA = 8 lma =
6
#5 x 2 - 2x + y - 8 = 0 Parabola: y = -(x - 1) 2 + 9 Center/Vertex: (1, 9) AOS: x = 1 DOO: down Focus: (1, 8 3/4) Directrix: y = 9 1/4 Parabola: y = -(x - 1) 2 + 9 Center/Vertex: (1, 9) AOS: x = 1 DOO: down Focus: (1, 8 3/4) Directrix: y = 9 1/4
7
#6 x 2 = 2x + y 2 - 4y + 7 Hyperbola Center: (1, 2) a = 2, b = 2, c = Vertices: (3, 2), (-1, 2) Foci: (1±, 2) Slopes of Asymptotes: ±1 Hyperbola Center: (1, 2) a = 2, b = 2, c = Vertices: (3, 2), (-1, 2) Foci: (1±, 2) Slopes of Asymptotes: ±1
8
#7 x 2 +4y 2 + 2x - 24y + 33 = 0 Ellipse Center: (-1, 3) a = 2, b = 1, c = Vertices:(-3, 3),(1, 3) Foci: LMA = 4 lma = 2 Ellipse Center: (-1, 3) a = 2, b = 1, c = Vertices:(-3, 3),(1, 3) Foci: LMA = 4 lma = 2
9
#8 x 2 + y 2 = x + 2 Circle Center: (1/2, 0) Radius= 3/2 Circle Center: (1/2, 0) Radius= 3/2
10
#9 Find f(x) + g(x) f(x) = x 2 -x+3 g(x) = x+8 f(x)+g(x) = (x 2 -x+3) + (x+8) f(x)+g(x) = x 2 + 11 f(x) = x 2 -x+3 g(x) = x+8 f(x)+g(x) = (x 2 -x+3) + (x+8) f(x)+g(x) = x 2 + 11
11
#10 Find f(x) - h(x) f(x) = x 2 -x+3 g(x) = x+8 f(x) - h(x) = (x 2 - x + 3) - (3x 2 +1) f(x) - h(x) = x 2 - x + 3 - 3x 2 - 1 f(x) - h(x) = -2x 2 - x + 2 f(x) = x 2 -x+3 g(x) = x+8 f(x) - h(x) = (x 2 - x + 3) - (3x 2 +1) f(x) - h(x) = x 2 - x + 3 - 3x 2 - 1 f(x) - h(x) = -2x 2 - x + 2
12
#11 Find f(g(x)) f(x) = x 2 -x+3 g(x) = x+8 f(x) = x 2 - x + 3 f(g(x)) =(x+8) 2 - (x+8) + 3 f(g(x)) = x 2 + 16x +64 - x - 8 + 3 f(g(x)) = x 2 +15x + 59 f(x) = x 2 -x+3 g(x) = x+8 f(x) = x 2 - x + 3 f(g(x)) =(x+8) 2 - (x+8) + 3 f(g(x)) = x 2 + 16x +64 - x - 8 + 3 f(g(x)) = x 2 +15x + 59
13
#12 Find f(h(x)) f(x) = x 2 -x+3 h(x) = 3x 2 +1 f(x) = x 2 - x + 3 f(h(x)) = (3x 2 +1) 2 - (3x 2 +1) + 3 f(h(x)) = 9x 4 +6x 2 +1-3x 2 -1+3 f(h(x)) = 9x 4 +3x 2 +3 f(x) = x 2 -x+3 h(x) = 3x 2 +1 f(x) = x 2 - x + 3 f(h(x)) = (3x 2 +1) 2 - (3x 2 +1) + 3 f(h(x)) = 9x 4 +6x 2 +1-3x 2 -1+3 f(h(x)) = 9x 4 +3x 2 +3
14
#13 Find g(f(x)) g(x) = x+8 f(x) = x 2 -x+3 g(x) = x + 8 g(f(x)) = (x 2 - x + 3) + 8 g(f(x)) = x 2 - x + 11 g(x) = x+8 f(x) = x 2 -x+3 g(x) = x + 8 g(f(x)) = (x 2 - x + 3) + 8 g(f(x)) = x 2 - x + 11
15
#14 Find h(f(x)) h(x) = 3x 2 +1 f(x) = x 2 -x+3 h(x) = 3x 2 + 1 h(f(x))= 3(x 2 - x + 3) 2 + 1 h(f(x))= 3(x 4 -2x 3 +4x 2 -3x+9)+1 h(f(x))= 3x 4 -6x 3 +21x 2 -18x+27+1 h(f(x))= 3x 4 -6x 3 +21x 2 -18x+28 h(x) = 3x 2 +1 f(x) = x 2 -x+3 h(x) = 3x 2 + 1 h(f(x))= 3(x 2 - x + 3) 2 + 1 h(f(x))= 3(x 4 -2x 3 +4x 2 -3x+9)+1 h(f(x))= 3x 4 -6x 3 +21x 2 -18x+27+1 h(f(x))= 3x 4 -6x 3 +21x 2 -18x+28
16
#15 Find h(g(x)) h(x) = 3x 2 +1 g(x) = x+8 h(x) = 3x 2 + 1 h(g(x)) = 3(x + 8) 2 + 1 h(g(x)) = 3(x 2 + 16x + 64)+1 h(g(x)) = 3x 2 + 48x + 192 + 1 h(g(x)) = 3x 2 + 48x + 193 h(x) = 3x 2 +1 g(x) = x+8 h(x) = 3x 2 + 1 h(g(x)) = 3(x + 8) 2 + 1 h(g(x)) = 3(x 2 + 16x + 64)+1 h(g(x)) = 3x 2 + 48x + 192 + 1 h(g(x)) = 3x 2 + 48x + 193
17
#16 Find f(-3) f(x) = x 2 - x + 3 f(-3) = (-3) 2 - (-3) + 3 f(-3) = 9 + 3 + 3 f(-3) = 15 f(x) = x 2 - x + 3 f(-3) = (-3) 2 - (-3) + 3 f(-3) = 9 + 3 + 3 f(-3) = 15
18
#17 Find h(f(4)) h(x) = 3x 2 +1 f(x) = x 2 -x+3 f(4) = (4) 2 - (4) + 3 f(4) = 15 h(x) = 3x 2 + 1 h(15) = 3(15) 2 + 1 h(f(4)) = 676 h(x) = 3x 2 +1 f(x) = x 2 -x+3 f(4) = (4) 2 - (4) + 3 f(4) = 15 h(x) = 3x 2 + 1 h(15) = 3(15) 2 + 1 h(f(4)) = 676
19
#18 Find g(h(2)) g(x) = x+8 h(x) = 3x 2 +1 h(2) = 3(2) 2 + 1 h(2) = 3(4) + 1 h(2) = 13 g(13) = 13 + 8 g(h(2)) = 21 g(x) = x+8 h(x) = 3x 2 +1 h(2) = 3(2) 2 + 1 h(2) = 3(4) + 1 h(2) = 13 g(13) = 13 + 8 g(h(2)) = 21
20
#19 Inverse of f(x) = 4x + 5 y = 4x + 5 x = 4y + 5 x - 5 = 4y x/4 - 5/4 = y y = 4x + 5 x = 4y + 5 x - 5 = 4y x/4 - 5/4 = y
21
#20 Inverse of g(x) = 3x 2 - 12 y = 3x 2 - 12 x = 3y 2 - 12 x + 12 = 3y 2 x/3 + 4 = y 2 y = 3x 2 - 12 x = 3y 2 - 12 x + 12 = 3y 2 x/3 + 4 = y 2
22
#21 f(x)=1/2x+2 g(x)=2x-4 f(g(x))=1/2(2x - 4) + 2 f(g(x)) = x - 2 + 2 f(g(x)) = x f(g(x))=1/2(2x - 4) + 2 f(g(x)) = x - 2 + 2 f(g(x)) = x
23
#22 f(x) = 3x-9 g(x) = -3x+9 f(x) = 3x-9 y = 3x - 9 x = 3y - 9 x + 9 = 3y x/3 + 3 = y Not equal to g(x) f(x) = 3x-9 y = 3x - 9 x = 3y - 9 x + 9 = 3y x/3 + 3 = y Not equal to g(x)
24
#23 {(1,3),(1,-1),(1,-3),(1,1)} {(3,1),(-1,1),(-3,1),(1,1)} Domain: 3, -1, -3, 1 Unique x - coordinates {(3,1),(-1,1),(-3,1),(1,1)} Domain: 3, -1, -3, 1 Unique x - coordinates
25
#24 Simplify Simplify:
26
#25Simplify Simplify
27
#26Simplify Simplify:
28
#27Simplify Simplify:
29
#28Absolute value equation Solve:
30
#29Absolute Value Inequality Solve:
31
#30 Find f(-5) If f(x) = 4x 3 - x + 1 f(-5) = 4(-5) 3 - (-5) +1 f(-5) = -500 + 5 + 1 f(-5) = -494 If f(x) = 4x 3 - x + 1 f(-5) = 4(-5) 3 - (-5) +1 f(-5) = -500 + 5 + 1 f(-5) = -494
32
#31Do the math (8x 3 + 2x 2 + 3x)÷(2x + 3)
33
#32Simplify Simplify:
34
#33Factor: 27a 3 + 125b 3 Factor:27a 3 + 125b 3 (3a + 5b)(9a 2 - 15ab + 25b 2 ) Factor:27a 3 + 125b 3 (3a + 5b)(9a 2 - 15ab + 25b 2 )
35
#34 Factor: 9x 2 - 12x + 4 Factor: 9x 2 - 12x + 4 (3x -2) 2 Factor: 9x 2 - 12x + 4 (3x -2) 2
36
#35Factor: 7y - 12x + 4xy - 21 Factor: 7y - 12x + 4xy - 21 7y - 21 + 4xy - 12x 7(y - 3) + 4x(y - 3) (y - 3)(7 + 4x) Factor: 7y - 12x + 4xy - 21 7y - 21 + 4xy - 12x 7(y - 3) + 4x(y - 3) (y - 3)(7 + 4x)
37
#36Factor: 15a 3 b - 5a 2 b 2 - 10ab 3 Factor: 15a 3 b - 5a 2 b 2 - 10ab 3 5ab(3a 2 - ab - 2b 2 ) 5ab(3a 2 - 3ab +2ab - 2b 2 ) 5ab[3a(a - b) + 2b(a - b)] 5ab(a - b)(3a + 2b) Factor: 15a 3 b - 5a 2 b 2 - 10ab 3 5ab(3a 2 - ab - 2b 2 ) 5ab(3a 2 - 3ab +2ab - 2b 2 ) 5ab[3a(a - b) + 2b(a - b)] 5ab(a - b)(3a + 2b)
38
#37Simplify: Simplify:
39
#38 Simplify: Simplify:
40
#39Simplify: Simplify:
41
#40Solve: Solve:
42
#41Solve:x 2 + 441 = 0 Solve: x 2 + 441 =0 x 2 = -441 x = x = ±21i Solve: x 2 + 441 =0 x 2 = -441 x = x = ±21i
43
#42Simplify: (9 - 3i) - (3 + 5i) (9 - 3i) - (3 + 5i) 9 - 3 - 3i - 5i 6 - 8i (9 - 3i) - (3 + 5i) 9 - 3 - 3i - 5i 6 - 8i
44
#43Simplify: (5 + 4i)(3 - 7i) Simplify: (5 + 4i)(3 - 7i) (5 + 4i)(3 - 7i) 15 - 35i + 12i - 28i 2 15 - 23i - 28(-1) 15 - 23i + 28 43 - 23i Simplify: (5 + 4i)(3 - 7i) (5 + 4i)(3 - 7i) 15 - 35i + 12i - 28i 2 15 - 23i - 28(-1) 15 - 23i + 28 43 - 23i
45
#44Simplify: Simplify:
46
#45Simplify: (7 - 3i)(7 + 3i) Simplify: (7 - 3i)(7 + 3i) 49 + 21i - 21i - 9i 2 49 - 9(-1) 49 + 9 58 Simplify: (7 - 3i)(7 + 3i) 49 + 21i - 21i - 9i 2 49 - 9(-1) 49 + 9 58
47
#46Simplify: i 10 i 21 i 30 Simplify: i 10 i 21 i 30 i 10+21+30 =i 61 = i 4(15)+1 = i 1 = i Simplify: i 10 i 21 i 30 i 10+21+30 =i 61 = i 4(15)+1 = i 1 = i
48
#47Simplify Simplify:
49
#48Solve: x 2 + 5x + 13 = 0 x 2 + 5x + 13 = 0
50
#49Solve: 6x 2 + 7x = 3 Solve:
51
#50Solve:2x 2 + 3x - 13 = 0 Solve:
52
#51 Word Problem h(t) = -16t 2 + 10t + 50 h(1) = -16(1) 2 + 10(1) + 50 h(1) = 44 feet 0 = -16t 2 + 10t + 50 h(t) = -16t 2 + 10t + 50 h(1) = -16(1) 2 + 10(1) + 50 h(1) = 44 feet 0 = -16t 2 + 10t + 50
53
#52 Simplify, combine like terms (4b 4 + 6b 2 - 3b + 5) - (2b 3 + 3b - 2) 4b 4 - 2b 3 + 6b 2 - 6b + 7 (4b 4 + 6b 2 - 3b + 5) - (2b 3 + 3b - 2) 4b 4 - 2b 3 + 6b 2 - 6b + 7
54
#53 Simplify, remove parentheses (y + 2)(y 2 - 4y + 1) y 3 - 4y 2 + y + 2y 2 - 8y + 2 y 3 - 2y 2 - 7y + 2 (y + 2)(y 2 - 4y + 1) y 3 - 4y 2 + y + 2y 2 - 8y + 2 y 3 - 2y 2 - 7y + 2
55
#54Do the arithmetic (2x 3 - 3x 2 + 4x - 5) ÷ (x - 2) Synthetic Division 2 2 -3 4 -5 4 2 12 2 1 6 7 2x 2 + x + 6x + 7/(x-2) (2x 3 - 3x 2 + 4x - 5) ÷ (x - 2) Synthetic Division 2 2 -3 4 -5 4 2 12 2 1 6 7 2x 2 + x + 6x + 7/(x-2)
56
#55 Factor 64x 2 y 2 - 25z 2 (8xy - 5z)(8xy + 5z) 64x 2 y 2 - 25z 2 (8xy - 5z)(8xy + 5z)
57
#56Find the zeros y = 3x 2 + 5x + 2 0 = 3x 2 + 5x + 2 0 = (3x 2 + 3x) + (2x + 2) 0 = 3x(x + 1) + 2(x + 1) 0 = (x + 1)(3x + 2) x = -1, -2/3 y = 3x 2 + 5x + 2 0 = 3x 2 + 5x + 2 0 = (3x 2 + 3x) + (2x + 2) 0 = 3x(x + 1) + 2(x + 1) 0 = (x + 1)(3x + 2) x = -1, -2/3
58
#57Find the max or min of #56 y = 3x 2 + 5x + 2 DOO: up, therefore a minimum x = -b/2a x = -5/2(3) = -5/6 y = 3(-5/6) 2 + 5(-5/6) + 2 y = 25/12 - 25/6 + 2 y = -1/12 Vertex is (-5/6, -1/12) y = 3x 2 + 5x + 2 DOO: up, therefore a minimum x = -b/2a x = -5/2(3) = -5/6 y = 3(-5/6) 2 + 5(-5/6) + 2 y = 25/12 - 25/6 + 2 y = -1/12 Vertex is (-5/6, -1/12)
59
#58 Solve Systems of Equations x + y = 2 x – 3y =6 -x-y=-2 x+(-1)=2 x-3y=6 x=3 -4y=4 y=-1 x + y = 2 x – 3y =6 -x-y=-2 x+(-1)=2 x-3y=6 x=3 -4y=4 y=-1
60
#59 (3x-5y=6)*7 21x-35y=42 (2x+7y=12)*5 10x+35y=60 (3x-5y=6)*7 21x-35y=42 (2x+7y=12)*5 10x+35y=60
61
#60 Solve Systems of Equations 7x+3y=-1 2x-y=9 y=2x-9 7x+3y=-1 2x-y=9 y=2x-9
62
#61 Solve a system 3x+2y=-24 6x-5y=30 -6x-4y=48 6x-5y=30 -9y=78 y=-78/9 3x+2y=-24 6x-5y=30 -6x-4y=48 6x-5y=30 -9y=78 y=-78/9
63
#62 Is (1, 2) a solution to the following system of inequalities? x>1, y 2x-1 1>1, 2 2(1)-1 Yes. Yes. No. The answer is NO. Is (1, 2) a solution to the following system of inequalities? x>1, y 2x-1 1>1, 2 2(1)-1 Yes. Yes. No. The answer is NO.
64
END of Review
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.